Menumbuhkan Sikap Siaga Bencana Melalui Pelatihan Pemadaman Api Ringan bagi Siswa SMAN 2 Tanjungpinang - Fathin Aulia Rahman; Munil Rizky Pratama; Widi Wahyudi; Marsin Marsin (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Indonesia is a country that faces a high risk of multiple disasters, one of which is fire disasters that can be prevented by the community through preparedness and early detection. The community service program, implemented by a team of lecturers and students from the Disaster Management Study Program at Budi Luhur University in collaboration with the Tanjungpinang SAR Office, conducted a basic fire extinguishing training session at SMAN 2 Tanjungpinang. The target audience for this training was students involved in the Scout, Paskibraka, and PKS (School Security Patrol) extracurricular activities, aimed at increasing student preparedness for fire emergencies. The activities included both theoretical materials and practical exercises on extinguishing fires and techniques for victim evacuation. The evaluation results showed an increase in participants' knowledge, particularly regarding the basic concepts of fire and victim movement, with understanding levels ranging from 45% to 100%, depending on the material. Although the results were positive, areas such as the type of fire extinguisher material and victim transfer techniques require further emphasis. This collaboration between educational institutions and disaster response agencies has proven effective in building student awareness to deal with emergency situations. Recommendations for future training include adopting a more interactive approach and incorporating intensive simulations to enhance students' understanding and readiness to face disaster.